THE ROLE OF SHARIA ACCOUNTING AND ITS RELEVANCE IN THE DIGITAL ERA IN GENERATION Z - Sri Wahyuni; Asmawarna Sinaga; Fauzi Ardianti (CV. Barokah Publsiher, 2024)
This study discusses the role of sharia accounting for Generation Z in the context of the digital era in Indonesia. The method used is a literature study from various academic sources related to sharia accounting, the characteristics of Generation Z, and digital transformation. The results of the study indicate that Generation Z is a digital native group that is very concerned with religious values and social justice. Sharia accounting, with the principles of transparency, justice, and sustainability, can be an important framework in managing the finances of this generation. Meanwhile, digitalization such as fintech, blockchain, and artificial intelligence opens up opportunities for efficiency and accessibility in sharia accounting, but also presents challenges for technical integration and data protection in accordance with Islamic principles. This study underlines the importance of sharia financial literacy for Generation Z and the need for technology-based educational innovation so that sharia principles remain relevant in modern accounting practices.